Tango in Japan : cosmopolitanism beyond the West - Asaba, Yuiko (Music and performing arts of Asia and the Pacific., 2025)
"Why do Japanese people love tango? Starting with this question, which the author frequently received while working as a tango violinist in Argentina, Tango in Japan reveals histories and ethnographies of tango in Japan dating back to its first introduction in the 1910s to the present day. While initially brought to Yokohama by North American tango dancers in 1914, tango's immediate popularity in Japan quickly compelled many Japanese performers and writers to travel to Argentina in search of tango's "origin" beginning in the 1920s. Many Japanese musicians, dancers, aficionados, and wider public have, since then, approached tango as a new vehicle of expression, entertainment, and academic pursuit. The sounds of tango provided comfort and a sense of hope to many during the most turbulent years of the twentieth century, carving out distinctive characteristics of contemporary Japanese tango culture. Bypassing the West-East axis of understanding cultural transmission, Tango in Japan uncovers the processes of attraction, rejection, and self-transformation, illuminating the tension of cosmopolitan endeavors away from the Euro-American West. Based on Asaba's field and archival work undertaken in both Japanese and Spanish languages in Japan and Argentina across two decades, and drawing on her own background as a tango violinist having performed as a member of tango orchestras in both countries, the discussions move between historical and ethnographic narratives, offering a comprehensive account of tango culture as it emerged in the history of a Japan-Argentina connection. Serving as the first in-depth work on the Japan-Argentina musical relation, Tango in Japan tells a story that reflects the modern transformations of Japan and Argentina, and global historical backdrops surrounding both countries"--